Planning protection of Ciechanow castle versus contemporary exposition in the landscape - Drobek, Katarzyna; Boguszewska, Kamila (Budownictwo i Architektura / Civil and Architectural Engineering, 2022)
The castle in Ciechanow is classified as a Gothic castle of the lowland type. The building, which is an example of defensive architecture, is located to the north of the historic urban layout of the Ciechanow centre. At present, the castle is covered by the following forms of protection: protection for the Natural and Landscape Complex "Łydynia River Valley”, provisions of the Local Spatial Development Plan and an entry in the Register of Historic Monuments. The authors of the paper analyse the legal regulations concerning the castle and their impact on the contemporary castle’s exposition in the landscape.